In vivo two-photon imaging reveals monocyte-dependent neutrophil extravasation during pulmonary inflammation - Kreisel, Daniel (National Academy of Sciences, 2010)
Immune-mediated pulmonary diseases are a significant public health concern. Analysis of leukocyte behavior in the lung is essential for understanding cellular mechanisms that contribute to normal and diseased states. Here, we used two-photon imaging to study neutrophil extravasation from pulmonary vessels and subsequent interstitial migration. We found that the lungs contained a significant pool of tissue-resident neutrophils in the steady state. In response to inflammation produced by bacterial challenge or transplant-mediated, ischemia-reperfusion injury, neutrophils were rapidly recruited from the circulation and patrolled the interstitium and airspaces of the lung. Motile neutrophils often aggregated in dynamic clusters that formed and dispersed over tens of minutes. These clusters were associated with CD115(+) F4/80(+) Ly6C(+) cells that had recently entered the lung. The depletion of blood monocytes with clodronate liposomes reduced neutrophil clustering in the lung, but acted by inhibiting neutrophil transendothelial migration upstream of interstitial migration. Our results suggest that a subset of monocytes serve as key regulators of neutrophil extravasation in the lung and may be an attractive target for the treatment of inflammatory pulmonary diseases.